1999
DOI: 10.1080/009841099158042
|View full text |Cite
|
Sign up to set email alerts
|

Coal Fly Ash-and Copper Smelter Dust-Induced Modulation of Ex Vivo Production of Tumor Necrosis Factor-Alpha by Murine Macrophages: Effects of Metals and Overload

Abstract: The objective of this study was to assess the effect of two arsenic-containing particles, coal fly ash (FA) and copper smelter dust (CU), on lung integrity and on the ex vivo release of tumor necrosis factor alpha (TNF-alpha) by alveolar phagocytes. Particle effects were compared in nonoverload condition on the basis of a low but identical volume load and arsenic content intratracheally instilled in the mouse lung (273 nl/mouse and 186 ng arsenic/mouse; FAL and CUL groups). Other mice received 600 ng arsenic/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The oxidative property of coal dusts is primarily attributed to its transition metal constituents, which typically include Fe, Cr, Co, Ni, Mn, As, Zn, and V (Broeckaert et al, 1999;Finkelman, 1999;Zhang et al, 2002). Using electron spin resonance (ESR), it was found that aqueous coal filtrates containing Fe, Zn, Cu, Ni, and Co were able to produce ROS such as • OH or ferryl (Fe IV =O) (Huang et al, 1993).…”
Section: Oxidative Property Of Coal Dustsmentioning
confidence: 98%
See 1 more Smart Citation
“…The oxidative property of coal dusts is primarily attributed to its transition metal constituents, which typically include Fe, Cr, Co, Ni, Mn, As, Zn, and V (Broeckaert et al, 1999;Finkelman, 1999;Zhang et al, 2002). Using electron spin resonance (ESR), it was found that aqueous coal filtrates containing Fe, Zn, Cu, Ni, and Co were able to produce ROS such as • OH or ferryl (Fe IV =O) (Huang et al, 1993).…”
Section: Oxidative Property Of Coal Dustsmentioning
confidence: 98%
“…Due to the mixed nature of various chemical compositions in these dusts, it is extremely difficult to identify the active compound(s) in the dusts that is responsible for the disease (Broeckaert et al, 1999;Costa & Dreher, 1997). Recently, progress has been made in metal-induced parenchymal lung disorders.…”
Section: Transition Metalsmentioning
confidence: 99%
“…Transition metals may enhance intracellular production of oxidants, with ensuing cell activation or injury. Metal-containing residual oil fly ash, coal fly ash, and some transition metals were found to result in enhanced expression of proinflammatory cytokines in cell culture systems (Broeckaert et al 1999;Dye et al 1999;Samet et al 1998;Smith et al 2000). However, there has been little direct evidence correlating cellular responses with ambient particle components.…”
mentioning
confidence: 99%
“…However, work by Broeckaet and colleagues has shown that coal fly ash can inhibit TNF-a release in alveolar macorophages (Broeckaert et al, 1999;Broeckaert et al, 1997). Work by Smith et al (2006) showed that rats exposed to high concentrations of PM 2.5 (1.4 mg/m 3 ) and PM 1 (600 µg/m 3 ) of coal fly ash for 4 hr/day for 3 days had a mild neutrophilic inflammatory response in the lungs and blood (Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…While recent, as well as earlier, reports have shown little to no adverse effects after inhalation exposure, others have shown that fly ash particles can activate alveolar macrophage and epithelial cells can cause the release of inflammatory mediators; can alter lung permeability; and can generate reactive oxygen species (ROS), enzymes such as elastase, proteases, and collagenases, cytokines such as TNF-a and MIP-1, and growth factors such as TGF-b (Borm, 1997;Fernandez et al, 2002;Fernandez et al, 2003;Broeckaert et al, 1999). However, work by Broeckaet and colleagues has shown that coal fly ash can inhibit TNF-a release in alveolar macorophages (Broeckaert et al, 1999;Broeckaert et al, 1997).…”
Section: Discussionmentioning
confidence: 97%